Ethnobiology of algarroba beer, the ancestral fermented beverage of the Wichí people of the Gran Chaco I: a detailed recipe and a thorough analysis of the process - Herrera Cano, Anahí Naymé (2020)
Algarroba (Prosopis alba) beer, known as aloja de algarroba (abbreviated aloja) in local Spanish, is the ancestral alcoholic beverage par excellence of the Wichís and other indigenous peoples of South American Gran Chaco, but nowadays is in disuse. Mentions on the recipe exist, but they are relatively few, concise and/or partial, and most of them were not registered within ethnobiological studies. The aims of this study were to (a) describe in detail the preparation process of algarroba beer and (b) analyse the process from a holistic approach, integrating Wichí concepts and biological explanations. Any morphological type of Prosopis alba fruits is useful, except those with poor mesocarp. Aloja must be prepared from relative fresh fruits, ground into pieces and not from flour alone. Through the senses, mainly taste and smell, the procedure is followed until optimal fermentation time is reached, which occurs at 24–48 h. When aloja is ready, it tastes tapay (bitter-sour) or nusuy (sour-salty). From the Wichí perspective, fermentation is both a maturation and a cooking process, and it is the “strength” (qahay, qahnayaj) of the pods, an intrinsic property, which allows fermentation to occur, with alcohol production. All interviewees’ remarks about the recipe are also explained by microbiological concepts. Altogether, results expand the knowledge on Wichí ethnobiology and are also useful to other disciplines interested in traditional food systems. Besides, they constitute a contribution to the rescue of the know-how on this traditional beverage for future generations and ultimately to food sovereignty.